SPE/DOE Improved Oil Recovery Symposium 2000
DOI: 10.2118/59290-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Oil Recovery Using a Low Concentration of Surfactant to Improve Spontaneous and Forced Imbibition in Chalk

Abstract: A study was undertaken with the objective of evaluating the use of low concentrations of surfactant to improve oil recovery. Various concentrations of commercial surfactants were screened for long term stability at high temperature in seawater. Cloud points, precipitation, and the stability of surface tension were used as screening criteria. Spontaneous imbibition tests at ambient and reservoir temperatures were conducted using reservoir chalk plugs that were moderately water-wet. A selected surfactant, when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…On average, about 80% of OOIP remains in fractured reservoirs after conventional waterflooding (Chen and Mohanty, 2013;Chen and Mohanty, 2015). The oil recovery from such reservoirs could be improved by altering the wettability of reservoir rocks to more water-wet state (Spinler et al, 2000;Adibhatla et al, 2005;Adibhatla and Mohanty, 2006;Kumar et al, 2008;Gupta and Mohanty, 2010).…”
Section: Wettability Alteration For Enhanced Oil Recoverymentioning
confidence: 99%
“…On average, about 80% of OOIP remains in fractured reservoirs after conventional waterflooding (Chen and Mohanty, 2013;Chen and Mohanty, 2015). The oil recovery from such reservoirs could be improved by altering the wettability of reservoir rocks to more water-wet state (Spinler et al, 2000;Adibhatla et al, 2005;Adibhatla and Mohanty, 2006;Kumar et al, 2008;Gupta and Mohanty, 2010).…”
Section: Wettability Alteration For Enhanced Oil Recoverymentioning
confidence: 99%
“…Hirasaki et al at Rice University, Houston, TX evaluated the use of a range of ethoxylated and propoxylayed alkyl sulfates (anionic surfactants) with sodium carbonate 12 to enhance oil recovery from fractured oil-wet carbonate rocks. The charge on calcite is positive below pH 9 and negative above pH 9.…”
Section: B) Anionic Surfactants Plus An Alkalimentioning
confidence: 99%
“…25;31 Several researchers reported that dilute solutions of chemical surfactants can alter the wettability of carbonate rock toward a more waterwet state. [6][7][8][9][10][11][12][13] This wettability change can improve oil recovery in fractured carbonate reservoirs by accelerating the spontaneous imbibition process during water flooding. They also reported that surfactant loss due to adsorption and/or retention on reservoir rock can be significant even at dilute surfactant concentrations.…”
Section: Evaluate the Biosurfactants For Improved Oil Recovery In Framentioning
confidence: 99%
See 1 more Smart Citation
“…There are many carbonate reservoirs in US (and the world) with light oil and fracture pressure below its minimum miscibility pressure (or reservoir may be naturally factured (Spinler et al, 2000), yet it was developed for sandstone reservoirs in the past (Bragg et al, 1982).…”
Section: Executive Summarymentioning
confidence: 99%